Immunotherapeutic Effects of Different Doses of Mycobacterium tuberculosis ag85a/b DNA Vaccine Delivered by Electroporation - Liang, Yan; Cui, Lei; Xiao, Li; Liu, Xiao; Yang, Yourong; Ling, Yanbo; Wang, Tong; Wang, Lan; Wang, Jie; Wu, Xueqiong (Frontiers in Immunology, 2022)
Background: Tuberculosis (TB) is a major global public health problem. New treatment methods on TB are urgently demanded. Methods: Ninety-six female BALB/c mice were challenged with 2×104 colony-forming units (CFUs) of MTB H37Rv through tail vein injection, then was treated with 10μg, 50μg, 100μg, and 200μg of Mycobacterium tuberculosis (MTB) ag85a/b chimeric DNA vaccine delivered by intramuscular injection (IM) and electroporation (EP), respectively. The immunotherapeutic effects were evaluated immunologically, bacteriologically, and pathologically. Results: Compared with the phosphate-buffered saline (PBS) group, the CD4+IFN-γ+ T cells% in whole blood from 200 µg DNA IM group and four DNA EP groups increased significantly (P<0.05), CD8+IFN-γ+ T cells% (in 200 μg DNA EP group), CD4+IL-4+ T cells% (50 μg DNA IM group) and CD8+IL-4+ T cells% (50 μg and 100 μg DNA IM group, 100 μg and 200 μg DNA EP group) increased significantly only in a few DNA groups (P< 0.05). The CD4+CD25+ Treg cells% decreased significantly in all DNA vaccine groups (P<0.01). Except for the 10 μg DNA IM group, the lung and spleen colony-forming units (CFUs) of the other seven DNA immunization groups decreased significantly (P<0.001, P<0.01), especially the 100 μg DNA IM group and 50 μg DNA EP group significantly reduced the pulmonary bacterial loads and lung lesions than the other DNA groups. Conclusions: An MTB ag85a/b chimeric DNA vaccine could induce Th1-type cellular immune reactions. DNA immunization by EP could improve the immunogenicity of the low-dose DNA vaccine, reduce DNA dose, and produce good immunotherapeutic effects on the mouse TB model, to provide the basis for the future human clinical trial of MTB ag85a/b chimeric DNA vaccine.